Unstable work histories and fertility in France: An adaptation of sequence complexity measures to employment trajectories - Daniel Ciganda (Demographic Research, 2015)
Background: The emergence of new evidence suggesting a sign shift in the long-standing negativecorrelation between prosperity and fertility levels has sparked a renewed interest in understanding the relationship between economic conditions and fertility decisions. In thiscontext, the notion of uncertainty has gained relevance in analyses of low fertility. So far, most studies have approached this notion using snapshot indicators such as type of contract or employment situation. However, these types of measures seem to be fallingshort in capturing what is intrinsically a dynamic process. Objective: Our first objective is to analyze to what extent employment trajectories have become lessstable over time, and the second, to determine whether or not employment instability has an impact on the timing and quantum of fertility in France.Additionally, we present a new indicator of employment instability that takes into account both the frequency and duration of unemployment, with the objective of comparing its performance against other, more commonly used indicators of economic uncertainty. Methods: Our study combines exploratory (Sequence Analysis) with confirmatory (Event History, Logistic Regression) methods to understand the relationship between early life-course uncertainty and the timing and intensity of fertility. We use employment histories from the three available waves of the Etude des relations familiales et intergenerationnelles (ERFI), a panel survey carried out by INED and INSEE which constitutes the base of the Generations and Gender Survey (GGS) in France. Results: Although France is characterized by strong family policies and high and stable fertility levels, we find that employment instability not only has a strong and persistent negative effect on the final number of children for both men and women, but also contributes to fertility postponement in the case of men.Regarding the timing of the transition to motherhood, we show how employment instability has a positive influence for women with more traditional views about the division of labor, and a negative influence among those with more egalitarian views.